ANALISIS KINERJA PETUGAS LAPANGAN KELUARGA BERENCANA PADA KANTOR BADAN KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN KABUPATEN DONGGALA - Rahmawati, Rahmawati (Katalogis, 2018)
Performance is one of the indicators in seeing the success of the organization and its employees in achieving the expected goals, including the performance of family planning field officers in providing family planning services to the community. To see the performance of family planning field officer in Donggala District, it is necessary to do research. The research method used descriptive qualitative. The number of informants in this study were seven people, who were drawn with the technique of purposive sampling. Techniques of collecting and retrieving data consists of observation, interviews, and documentation. The theory used is Performance developed by Lexie Giroth which states that to measure performance can be seen from the indicators of Ability, Motivation and Discipline. The results showed that the performance of family planning field officers at the Office of Family Planning and Women Empowerment Donggala District is less than optimal because of the three aspects of performance developed by Lexie Giroth, only two aspects are good aspects of motivation and discipline aspects. While the ability aspect is not optimal because the number of limited implementing officer make the ability to give service to acceptor less than optimal